(untitled) (Música Hodie, 2025)
This review examines Tracing the History of Wind Bands in Macau (2025), a landmark contribution by Dai Ding Cheng and Sio-keong Hong that explores the development of wind bands in Macau from 1600 to 1950, positioning the city as a gateway for Western music into China; drawing on archival sources, photographs, and press materials, it reveals the multiracial fabric of Macau’s musical life, the influence of churches, military and police bands, and the emergence of school ensembles, while filling a major gap by documenting Chinese participation in pre-war wind bands and offering valuable insights for Chinese music historiography and cultural exchange studies.